Time series of atmospheric methane and carbon dioxide concentrations measured during POSEIDON cruise POS533 - Tim Weiß; Jens Greinert; Birgit Quack (PANGAEA, 2020)
The atmospheric CO? and CH4 concentrations were monitored throughout the cruise using a cavity ring down spectrometer (CRDS, Picarro G2301-f) and GEOMARs extquotesingleAtmospheric Intake System extquotesingle (AIS).